Efecto bioestimulante de Trichoderma harzianum rifai en semillas de Clitoria ternatea sometidos a diferentes periodos de frio y remojo. - Pastuña Toaquiza, Diana Vanessa (2022)
The present research project was developed in La Maná, in the sector of La Playita, here it was sought to analyze the effect of soaking time in solutions of Trichoderma harzianum rifai in the emergence of Clitoria ternatea seeds subjected to different periods of cold; to establish the best soaking time in solutions of Trichoderma harzianum rifai for Clitoria ternatea seeds; to determine the best soaking time in solutions of Trichoderma harzianum rifai for Clitoria ternatea seeds. To determine the adequate soaking time in Trichoderma harzianum rifai solutions for Clitoria ternatea seeds and to evaluate some agronomic variables of Clitoria ternatea obtained from these treatments. For this, a factorial DCA with 24 treatments was used. The results in terms of emergence showed that both the cold factor and hours of soaking influenced this process and that the best treatment was T9 (0 days of cold and 3 hours of soaking in trichoderma) with a percentage of 43.33%. In the case of days to emergence, it was noted that the treatments subjected to a shorter period of cold or none (0 and 10 days) took 4 days to emerge, while those of 20 and 30 days did it in 6. For the mortality variable, on the other hand, it was observed that the seeds that suffered this event, did it by external factors and not by the influence of any of the factors under study. For the rest of the morphological variables, it was shown that the interaction between the factors had a positive influence but that, when analyzed independently, the days of cold had a positive effect on the variables of seedling height, stem diameter, length of functional leaves and number of functional leaves at 30 days, root length, root weight, root volume, and dry matter, resulting in T9 as the best treatment in all cases. This could be associated with the fact that the cold factor influenced embryo development and that being subjected to long periods of cold slows down its metabolism and the seed emergence process.